Relationship Between Women’s Futsal Athletes Life and Competition Performance - Nuraeni, Diana; Sugiarto, Bambang Gatot (STKIP Paasundan Press, 2024)
The purpose of this study was to determine the relationship between the lifestyle of women's futsal athletes and their performance in competition. The method used is correlational with a quantitative approach. The population of this study was 50 UKM futsal athletes (Student Activity Unit) STKIP Pasundan Cimahi, the sampling used was purposive sampling, the sample used was 14 UKM futsal athletes (Student Activity Unit) STKIP Pasundan Cimahi. Data collection or instruments used are questionnaires or questionnaires and the format of GPAI analysis (Game Performance Assessment Instrument). The hypothesis data analysis technique is accepted, meaning that there is a relationship between the lifestyle of female futsal athletes and competitive performance with an average lifestyle score of 119 and competitive performance with an average value of 65%.